Biochemical‐ and Biophysical‐Induced Barriergenesis in the Blood–Brain Barrier: A Review of Barriergenic Factors for Use in In Vitro Models. Issue 5 (4th March 2021) - Schofield, Christina L.; Rodrigo-Navarro, Aleixandre; Dalby, Matthew J.; Van Agtmael, Tom; Salmeron-Sanchez, Manuel
Abstract : Central nervous system (CNS) pathologies are a prevalent problem in aging populations, creating a need to understand the underlying events in these diseases and develop efficient CNS‐targeting drugs. The importance of the blood–brain barrier (BBB) is evident, acting both as a physical barrier to drug entry into the CNS and potentially as the cause or aggravator of CNS diseases. The development of a biomimetic BBB in vitro model is required for the understanding of BBB‐related pathologies and in the screening of drugs targeting the CNS. There is currently great interest in understanding the influence of biochemical and biophysical factors, as these have the potential to greatly improve the barrier function of brain microvascular endothelial cells (BMECs). Recent advances in understanding how these may regulate barriergenesis in BMECs help promote the development of improved BBB in vitro models and therefore novel interventional therapies for pathologies related to its disruption. Herein, an overview of specific biochemical and biomechanical cues in the formation of the BBB, with a focus on in vitro models and how these might recapitulate the BBB function, is provided. Abstract : In vitro models for the blood–brain barrier (BBB) are vital for the development of CNS‐targeting drugs. However, there is a lack of suitable biomimetic models. Herein, the state of the art of these models, focusing on biochemical/physical signals and how these either aid in the formation of the barrier or maintain the blood–brain barrier (BBB), is recapitulated.